Post a New Question


posted by .

Perform the addition or subtraction.

tanx - sec^2x/tanx

tan^2(x)/tan(x) - sec^2x/tanx =

tan^2x sec^2x / tanx

then I use the identity 1+tan^2u=sec^2u

I do not know what to do at this point.

  • Pre-Cal -

    from you second line
    tan^2(x)/tan(x) - sec^2x/tanx
    = (tan^2 x - sec^2 x)/tanx
    = (tan^2 x - (1 + tan^2 x))/tanx
    = -1/tanx or -cotx or -sinx/cosx

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question